Impacts and implications of agronomic efficiency on rice and maize productivity among small-scale farmers in Chiang Mai, Thailand - Qinbin Yu; Thi Phuoc Lai Nguyen; Rajendra P. Shrestha; Vilas Nitivattananon (Cogent Food & Agriculture)
Agricultural productivity (APL) and efficiency are crucial for Thailand’s development, yet local small-scale farmers face challenges due to lower production. This study compares the efficiency of agronomic practices between rice and maize cultivation. Utilizing survey data from 297 small-scale farmers across three districts in Chiang Mai, we employed the Frontier Production Function and integrated kernel density analysis to assess agronomic practices. Results indicate maize cultivation is slightly more efficiency than rice. Technological progress, particularly advanced labor, significantly impacts productivity in both crops. Kernel density analysis reveals clustering of efficient values around intervals associated with advanced labor practices, emphasizing the importance of promoting technological progress. Meanwhile, the concentration of KDE implies a higher density of efficiency values within these intervals, representing typical levels of agronomic practices’ efficiency or reflecting common technological and managerial practices. Tobit regression analysis shows farm size, family size, market distance and agricultural revenue are important determinants for rice productivity; by contrast, farm size and income are important factors for maize output. The study emphasizes how the efficiency of maize and rice is impacted differently by inputs and social factors. These understandings can help policymakers maximize agricultural inputs and solve social issues to improve sustainability and production.